METODE PENELITIAN ILMIAH BERBASIS FILSAFAT ILMU - Maulida, Ratna Siti; Fauziah, Siti Syifa; Muiz, Rizqi Nurlaili; Fauzi, Anis; Hidayat, Wahyu (Jurnal Manajemen Pendidikan, 2024)
The philosophy of science-based scientific method refers to a research approach that not only relies on technical and systematic procedures,but is also based on philosophical principles that underline the understanding of knowledge, reality and truth. This research aims to examine and develop scientific research methods based on an understanding of the philosophy of science, leading to improved quality and understandability in the scientific research process. The main objective of this research is to identify the basic principles contained in the philosophy of science, as well as its application in a more comprehensive scientific method. This research was conducted using a qualitative approach, through literature review and analysis of philosophical concepts related to the scientific method. The research process involved an in-depth analysis of the theories and characteristics of philosophy of science, such as ontology, epistimology, methodology, ethical values, history, context, principles, theory, critical, reflective, and interdisciplinary. The results show that the philosophy of science approach can provide a more solid foundation in determining research methodology, strengthen the validity and objectivity of the results, and open space for critical thinking in dealing with the complexity of scientific problems. The novelty of this research lies in the development of integration between the scientific method and the values of philosophy of science that have been neglected so far, with the hope that it can improve the quality of scientific knowledge.